Discovering Australia Through Fiction: French Translators as Aventuriers - Frank, Helen (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2006)
AbstractThe translation into French of referents of Australia and Australianness in fiction necessitates a considerable variety of translational tendencies and interpretive choices. This study focuses on French translations of selected passages and blurbs from Australian fiction set in regional Australia to determine how referents of Australian flora, fauna, landscape and people are translated and interpreted in a non-English speaking cultural system. Guided by concerns for the target readers’ understanding of the text, French translators employ normative strategies and adaptive procedures common to translation to enhance reader orientation. There is, nonetheless, evidence of culture-specific appropriation of the text and systematic manipulation of Australian referents that goes beyond normative solutions. Such appropriation and manipulation stem from a desire to create and foster culture-specific suppositions about Australia consistent with French preoccupations with colonialism, the exotic, exploration and adventure.